Health and local food consumption in cross-cultural tourism mobility: an assemblage approach. Issue 6 (10th November 2022) - Lin, Jiayi; Cui, Qingming; Xu, Honggang; Guia, Jaume
Abstract: A healthy diet is vital to sustaining tourist mobility. In cross-cultural mobility, tourists must face strange local eating environments in tourism place and the complex health problems that these environments may cause. Existing research on tourist food consumption and health mainly addresses health from a biomedical perspective by emphasizing food nutrition and hygiene. We adopt an assemblage approach to understanding health as a relational outcome determined by multiple material, psychological, and cultural dimensions. Using Chinese outbound travel to Spain as a case, we explore how psychology, dietary habits, and cultural beliefs interconnect with the foods in novel cross-cultural environments to generate healthiness. A semi-structured interview method was used to collect data in Barcelona and Madrid. We construct three formulas to illustrate the health assemblages in tourists' food consumption. In the food-psychology assemblage, tourists believe that low-risk foods are healthy. Neophobic tourists avoid tasting novel local foods due to unknown health risks, whereas neophiliac tourists show fewer similar health concerns. In the food-dietary habits assemblage, healthy dieting is the habitual and comfortable diet. Tourists with Chinese dietary habits are uncomfortable eating novel local foods. Cosmopolitan tourists, who incorporate various food habits in their diet, switch freely between different foods to obtain health. In the food-cultural beliefs assemblage, traditional Chinese cultural beliefs of yin-yang balance affect tourists' health experience through diet. Tourists carefully choose local foods to achieve a cold-hot balance to keep health. These three health assemblages indicate that food health in tourism is a relational result of multiple dimensions. 摘要: 健康饮食对于旅游流动至关重要。在跨文化旅游流动中, 游客在旅游地会面对陌生的饮食环境, 以及这些环境可能引起的复杂健康问题。既有关于旅游食物消费与健康的研究主要是从生物医学的角度来理解食物的健康, 强调食物的营养与卫生。我们采用组装视角, 将健康理解为由物质、心理和文化等多种维度决定的关系性结果。以中国游客赴西班牙的出境游为例, 我们探讨了饮食心理、饮食习惯和文化信仰如何在新奇的跨文化环境中与食品相互联系, 从而生产饮食健康。我们采用半结构式访谈法在巴塞罗那和马德里收集数据。我们构建了三个公式来说明旅游食物消费中的健康组装。在食物-心理组装中, 低风险食物被认为是健康的。具有恐新心理的游客会避免品尝新奇的当地食物, 担心其有未知的健康风险。喜新的游客则较少具有类似的健康担忧。在食物-饮食习惯组装中, 健康饮食被认为是令人舒适的习惯性饮食。根植中国饮食习惯的游客因不习惯于消费当地新奇食物会出现身体不适。世界主义游客因已融入多种饮食文化习惯, 他们可以自由地在不同食物之间切换以保持健康。在食物-文化信仰组装中, 中国传统阴阳平衡的文化观念影响游客对食物健康的体验。游客精心选择当地食物, 以搭配食物的冷热均衡, 从而获得健康。这三个健康组装证明旅游饮食健康是多维度的关系性结果。